2006
DOI: 10.1002/ejoc.200600838
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Synthesis of Antithrombotic Agents M58163 and M58169: Dynamic Kinetic Resolution in Amide Formation Catalyzed by La‐Linked BINOL Complex

Abstract: The first asymmetric syntheses of antithrombotic agents M58163 and M58169 are reported. Dynamic kinetic resolution is observed in the amide formation step.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Saitoh, Mikami, and co-workers completed the asymmetric total syntheses of M58163 ( 303 ) and M58169 ( 304 ), both of which display antithrombotic activity (Scheme ). Access to their imidazopyrazinone core ( 301 ) was achieved using a lanthanum-catalyzed asymmetric cascade cyclization proceeding through racemic aminal 302 . , Mechanistic studies revealed that the aminal is formed reversibly, with enantioselection occurring during the La-catalyzed amide bond-forming step. A survey of various lanthanide metal complexes revealed that the La-linked BINOL complex 294 (Figure ) gave the best yield and selectivity.…”
Section: Dynamic Kinetic Asymmetric Transformationsmentioning
confidence: 99%
“…Saitoh, Mikami, and co-workers completed the asymmetric total syntheses of M58163 ( 303 ) and M58169 ( 304 ), both of which display antithrombotic activity (Scheme ). Access to their imidazopyrazinone core ( 301 ) was achieved using a lanthanum-catalyzed asymmetric cascade cyclization proceeding through racemic aminal 302 . , Mechanistic studies revealed that the aminal is formed reversibly, with enantioselection occurring during the La-catalyzed amide bond-forming step. A survey of various lanthanide metal complexes revealed that the La-linked BINOL complex 294 (Figure ) gave the best yield and selectivity.…”
Section: Dynamic Kinetic Asymmetric Transformationsmentioning
confidence: 99%
“…We report here the full account of the dynamic kinetic resolution in the amide formation step following formation of a cyclic N,N-acetal leading to the tricyclic key intermediate of M58163 and M58169 (Scheme 2). [10] Results and Discussion Enantioselective Cyclic N,N-Acetal Formation First, the chiral Brønsted acids and salen-manganese complex, by which the cyclic N,O-acetal had been obtained enantioselectively, [4] were examined. The results are summarized in Table 1.…”
Section: Introductionmentioning
confidence: 99%